Regeneration of plants from anther, callus and protoplast cultures of rice (Oryza sativa L.) - Nahar, Maksuda Anjuman (1994)
The work described in this thesis focuses on the development of fully reproducible systems of plant regeneration through embryogenic callus and totipotent protoplast cultures of rice (Oryza sativa L. cv. Taipei 309). The calli originated from different explants, including excised anthers, isolated microspores, mature seed-embryos, immature seed-embryos and leaf-base meristems. In the callus culture and plant regeneration studies, excised anther-derived callus produced higher numbers of green (90.5%) and albino (9.5%) plants, both haploids (81.2%) and diploids (18.8%), compared to other explants. The plant regeneration frequency from mature seedembryo-derived callus varied with callus age and embryogenicity of the callus. A maximum of 20% plant regeneration was obtained with approx. 2% of the regenerated plants being albinos. In the case of mature or immature seed-embryos and leaf-base meristems, plant regeneration frequency from callus was dependent on some more specific factors, in addition to callus age and embryogenicity. These factors were the age of seedlings grown in vitro and the age of immature embryos after anthesis for leaf-base meristem and immature embryo cultures, and also the scutellar surface orientation of mature or immature embryos during callus culture initiation. The present study also focused on the plating efficiencies and plant regeneration frequencies obtained from culture of embryogenic cell suspension-derived protoplasts. These varied with the explant source, the embryogenic nature and age of the callus during suspension initiation, the age of the embryogenic suspension culture, the time of enzymatic digestion, the plating density, viability of protoplasts and use of the suspensions at their exponential (actively dividing) growth stage. The results from this study indicated that leaf-base meristem and anther calli-derived suspensions retain their regenerability for a longer time compared to suspensions derived from mature seedscutellum and immature seed-derived embryos. Maximum plant regeneration frequency (45%) was obtained from embryogenic suspensions derived from mature seedembryos. A detailed study of different agronomic characteristics of 57 protoclonal plants (mature seed-scutellum-derived) was performed and the statistical analysis of the data indicated a range of variability among the protoclonal plants and also between the protoclonal and seed-derived plants. A detailed study of the ploidy levels of regenerated plants obtained through different culture systems (callus and protoplasts) was performed by flow cytometry and chromosome counting of meristematic cells. The results showed that anther calliderived plants were mostly haploids, protoplast-derived plants of leaf-base meristem, anther, and mature seed-scutellum origin were mostly tetraploids and in between these two groups, diploids, triploids and aneuploids were also present.